MR Imaging in the Differential Diagnosis of Neurogenic Foot Drop - Bendszus, Martin (AJNR Am J Neuroradiol, 2003)
BACKGROUND AND PURPOSE: Prolonged T2 relaxation time of denervated muscle has been described in several clinical and experimental studies. The purpose of this study was to evaluate the utility of MR imaging in the diagnosis of neurogenic muscle disorders compared with that of clinical and electrophysiologic examination. METHODS: In a prospective study, 40 consecutive patients clinically presenting with a foot drop were included. MR imaging of the lower leg included axial T1-weighted and axial turbo inversion recovery magnitude (TIRM) sequences. Two readers blinded to clinical data evaluated T1-weighted images for anatomic localization of affected muscles and TIRM images for patterns of signal intensity increase. After MR imaging, a detailed neurophysiologic examination was performed. Cause of foot drop was independently determined on the basis of MR and electrophysiologic data. RESULTS: Clinical examination and electromyography (EMG) disclosed 20 peroneal nerve lesions, nine cases of L5 radiculopathy, and 11 nerve lesions extending beyond neural structures. MR imaging revealed three distinct patterns of signal intensity increase on TIRM images: peroneal nerve pattern, L5 pattern, and unspecific pattern. MR imaging and EMG findings were in agreement in 37 (92%) of 40 patients. In three patients, MR imaging revealed a more widespread involvement than did EMG. In one of these patients, denervation in the corresponding muscle was validated by follow-up EMG. No false-negative diagnoses were made by use of MR imaging as compared with use of EMG. CONCLUSION: MR imaging improves accuracy in the differential diagnosis of peripheral nerve lesions compared with that of EMG and can supplement EMG in the diagnosis of denervated muscles.